“… Murtaza-Ali Ogly”. (Concerning the origin of Chilla and Magomad Murtazalievs) - Sergey V. Talantov (Историческое оружиеведение)
Museum and private collections contain kindjals and shashkas of 1880-1910’s with the Cyrillic inscription “CHILLA” that are attributed as items crafted by Chilla Murtazaliev’s workshop.